STRATEGI PEMBELAJARAN BAHASA ARAB BERBASIS RESOURCE BASED LEARNING - Nur Sholeh (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2012)
Learning is a process of interaction in fact against all situations that exist around the individual. Learning can be seen as processes that are directed toward the purpose and process of doing through a variety of experiences. Learning is also a process view, observe and understand something. Learning activities performed by two people, educators and learners. Educators are teaching behavior and the behavior of learners are learning. Teaching learning behavior and behavior are associated with learning materials. Learning materials can be in the form of knowledge, values, morality, religion, art, attitude and skills. The relationship between educators, learners, and materials are dynamic and complex. To achieve success in learning activities, there are several components that can support, i.e., objective component component component materials, teaching and learning strategies, and evaluation components. Each of these components are interrelated and mutually influence each other. Resource-based learning is any form of learning that directly confronts learners with something or some sources learn individually or groups with all learning activities related to it, so it's not the conventional way where educators convey materials lessons to students.